Spesies-Spesies Tumbuhan Famili Asteraceae Di UIN Antasari Banjarmasin - Agustina Ambar Pertiwi; Sari Indriyani; Kasmiyah Kasmiyah (Universitas Sebelas Maret, 2025)
This study aims to identify the types of plants of the Asteraceae family in the environment of UIN Antasari Banjarmasin. This type of research is field research with a qualitative-quantitative descriptive research approach. The research population is all plants of the Asteraceae family in the environment of UIN Antasari Banjarmasin, the research sample is plants of the Asteraceae family in the environment of UIN Antasari Banjarmasin which were found by the exploration method and observation-documentation techniques to collect data. Data were analyzed descriptively exploratory using relevant literature. The results of the study found 11 species of plants of the Asteraceae family, namely Syndrella nodiflora Gaertn., Eclipta prostrata, Emilia sonchifolia, Cyanthilium cinereum L., Ageratum conyzoides, Mikania micrantha Kunth., Sphagneticola trilobata L., Gynura divaricata L., Bidens pilosa L., Cosmos caudatus Kunth., and Zinnia peruviana.